Insights from transient absorption spectroscopy into electron dynamics along the Ga-gradient in Cu(In,Ga)Se2 solar cells - Chang,Y-H; Carron,R; Ochoa,M; Bozal-Ginesta,C; Tiwari,AN; Durrant,J; Steier,L (Advanced Energy Materials, 2021)
Cu(In,Ga)Se2 solar cells have markedly increased their efficiency over the last decades currently reaching a record power conversion efficiency of 23.3%. Key aspects to this efficiency progress are the engineered bandgap gradient profile across the absorber depth, along with controlled incorporation of alkali atoms via postdeposition treatments. Whereas the impact of these treatments on the carrier lifetime has been extensively studied in ungraded Cu(In,Ga)Se2 films, the role of the Gagradient on carrier mobility has been less explored. Here, transient absorption spectroscopy (TAS) is utilized to investigate the impact of the Gagradient profile on charge carrier dynamics. Minority carriers excited in large Cu(In,Ga)Se2 grains with a [Ga]/([Ga]+[In]) ratio between 0.2–0.5 are found to driftdiffuse across ≈1/3 of the absorber layer to the engineered bandgap minimum within 2 ns, which corresponds to a mobility range of 8.7–58.9 cm2 V−1 s−1. In addition, the recombination times strongly depend on the Gacontent, ranging from 19.1 ns in the energy minimum to 85 ps in the high Gacontent region near the Moback contact. An analytical model, as well as driftdiffusion numerical simulations, fully decouple carrier transport and recombination behaviour in this complex compositiongraded absorber structure, demonstrating the potential of TAS.